The Promise of Index Insurance - Gine, Xavier (World Bank, Washington, DC, 2012)
The third in new series of impact notes highlights an example of where randomized experiments have been used to help understand the impact of a new insurance product first developed by Commodity Risk Management Group (CRMG) at the World Bank and various public and private partners in several client countries.